1986
DOI: 10.1017/s0022112086000393
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on vertical plane buoyant jets in shallow water

Abstract: The paper reports on measurements of the flow generated by a plane buoyant jet discharging vertically into shallow water. The study comprises visualization experiments, mean-velocity and turbulence measurements with a two-channel laser-Doppler anemometer and temperature measurements with thermistor probes. According to the previous investigation of Jirka & Harleman (1979) (JH) the flow may be either stable with the heated discharge water leaving the near field in a warm water layer adjacent to the surface, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
4
8
1
Order By: Relevance
“…At tðV 1 =D i Þ ¼ 54:6 and 70.2, the general horizontal movement of the flow motion leads to the occurrence of additional two recirculating cells having lower magnitude with respect to the cells close to the jet injection. This kind of process can also be observed in the cases of water-jet phenomena in unconfined conditions (without the presence of vertical walls) in which the development of more recirculating cells along the fluid domain is highlighted (Andreopoulos et al, 1986). As pointed out by the experiments of Espa and Frattini (2002) and Andreopoulos et al (1986), the horizontal length of the recirculating cells in the present SPH simulations has an extension which ranges between 2H s and 2.5H s .…”
Section: Jet Injected At the Bottom Of A Water Tanksupporting
confidence: 77%
See 2 more Smart Citations
“…At tðV 1 =D i Þ ¼ 54:6 and 70.2, the general horizontal movement of the flow motion leads to the occurrence of additional two recirculating cells having lower magnitude with respect to the cells close to the jet injection. This kind of process can also be observed in the cases of water-jet phenomena in unconfined conditions (without the presence of vertical walls) in which the development of more recirculating cells along the fluid domain is highlighted (Andreopoulos et al, 1986). As pointed out by the experiments of Espa and Frattini (2002) and Andreopoulos et al (1986), the horizontal length of the recirculating cells in the present SPH simulations has an extension which ranges between 2H s and 2.5H s .…”
Section: Jet Injected At the Bottom Of A Water Tanksupporting
confidence: 77%
“…Due to the presence of a shallow water ambient (low ratio between water depth of the tank and jet diameter), the zone of surface impingement is characterized by two small standing waves appearing beside the vertical motion of the jet (0:4 o x=L o0:6), as described in Espa and Frattini (2002) and Kuang et al (2001). In this case, the fluid is entrapped generating two recirculating counter-rotating cells (Andreopoulos et al, 1986) (see streamlines in Fig. 15).…”
Section: Jet Injected At the Bottom Of A Water Tankmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been proposed for generation of the vortices (Andreopoulis et al, 1986). In the case above, the vortices are part of a horseshoe-shaped vortex system caused by rotation around the rising plume in the near field that persists into the far field, gradually moving apart.…”
Section: Classic Plume Behaviourmentioning
confidence: 99%
“…There appear to be no conclusive results defining the conditions under which bifurcation appears, but it is sensitive to a number of factors including discharge rate, buoyancy, outfall shape and diameter, and depth and velocity of the ambient fluid above the outfall (Andreopoulis et al, 1986;Jirka and Domeker, 1991;Smith and Mungal, 1998). In considering spreading of the plume observed at Sizewell A power station (Suffolk, UK), MacQueen (1978) concluded that vortices related to buoyancy were more likely to be significant than velocity shear at the outlet.…”
Section: Classic Plume Behaviourmentioning
confidence: 99%